Naturalist - Wilson, Edward Osborne, 1929- (Washington, D.C. : Island Press, 1994)
Harvard University professor, Edward Wilson, describes his growth as a scientist and the evolution of the science of entomology.
Includes index.
Booklist starred.
Library Journal.
Publisher's Weekly.
Adult.
Adult
Keywords: Wilson, Edward Osborne, -- 1929-; Wilson, Edward Osborne, -- 1929-; Naturalists -- United States -- Biography; Naturalists -- Biography